ALLELOPATHIC EFFECT OF AQUEOUS EXTRACTS OF CALOTROPIS PROCERA ON GERMINATION AND SEEDLING GROWTH OF MAIZE (Biological Sciences - PJSIR, 2004)
The effects of 24 and 48 h leaf extracts of Calotropis procera on radicle and plumule growth of four cultivars of maize (Oba Super I, II, III and IV) were examined. Both extracts demons- trated considerable inhibitory effects on the growth of radicle and plumule of the cultivars and the severity of the inhibition was observed to increase with the increase in the duration of the extraction.